Adaptive PID Control of Wind Turbines for Power Regulation with Unknown Control Direction and Actuator Faults - Habibi, H.; Nohooji, H.; Howard, Ian (IEEE Access, 2018)
Proportional integral derivative (PID) regulators are the most practical control schemes for industrial wind turbines. The key to PID design is the determination of the control parameter gains, which motivated our attempts to construct an adaptive PID control for wind turbines allowing auto-tuning of the gains without the need for trial and error processes. By equipping a novel PID-based fault-tolerant controller with a Nussbaum-type function, a robust adaptive and fault-tolerant control scheme is developed for wind turbines. Compared with available methods, the proposed controller has advantages such as, ability for dealing with complete nonlinear dynamics of wind turbines including model uncertainty, ability to ensure system stability by using an adaptive self-tuning gain algorithm, and robustness against wind speed variation. Furthermore, it has the ability to accommodate unexpected actuator faults and the accommodation of an unknown control direction. However, the salient feature of the proposed controller lies in its simple structure and inexpensive online computational demands while dealing with the nonlinear dynamics of wind turbines and unknown disturbances. It is shown that the proposed pitch angle controller remains continuous and smooth and all the closed-loop system signals are guaranteed to be uniformly ultimately bounded. Theoretical analysis and numerical simulations are presented to confirm the effectiveness of the proposed control strategy.